Three-dimensional image reconstruction of insect flight muscle. II. The rigor actin layer (The Rockefeller University Press, 1989)
The averaged structure of rigor cross-bridges in insect flight muscle is further revealed by three-dimensional reconstruction from 25-nm sections containing a single layer of thin filaments. These exhibit two thin filament orientations that differ by 60 degrees from each other and from myac layer filaments. Data from multiple tilt views (to +/- 60 degrees) was supplemented by data from thick sections (equivalent to 90 degrees tilts). In combination with the reconstruction from the myac layer (Taylor et al., 1989), the entire unit cell is reconstructed, giving the most complete view of in situ cross-bridges yet obtained. All our reconstructions show two classes of averaged rigor cross- bridges. Lead bridges have a triangular shape with leading edge angled at approximately 45 degrees and trailing edge angled at approximately 90 degrees to the filament axis. We propose that the lead bridge contains two myosin heads of differing conformation bound along one strand of F-actin. The lead bridge is associated with a region of the thin filament that is apparently untwisted. We suggest that the untwisting may reflect the distribution of strain between myosin and actin resulting from two-headed, single filament binding in the lead bridge. Rear bridges are oriented at approximately 90 degrees to the filament axis, and are smaller and more cylindrical, suggesting that they consist of single myosin heads. The rear bridge is associated with a region of apparently normal thin filament twist. We propose that differing myosin head angles and conformations consistently observed in rigor embody different stages of the power stroke which have been trapped by a temporal sequence of rigor cross-bridge formation under the constraints of the intact filament lattice.